2012
DOI: 10.4161/cc.20437
|View full text |Cite
|
Sign up to set email alerts
|

Heterochronic parabiosis for the study of the effects of aging on stem cells and their niches

Abstract: Aging is unmistakable and undeniable in mammals. Interestingly, mice develop cataracts, muscle atrophy, osteoporosis, obesity, diabetes and cognitive deficits after just 2-3 postnatal years, while it takes seven or more decades for the same age-specific phenotypes to develop in humans. Thus, chronological age corresponds differently with biological age in metazoan species and although many theories exist, we do not understand what controls the rate of mammalian aging. One interesting idea is that species-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
215
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(230 citation statements)
references
References 63 publications
15
215
0
Order By: Relevance
“…29 30 These factors can accelerate the accumulation of unrepaired molecular damage and senescent cells, stimulate the DNA damage response, inhibit stem cell regenerative function, and promote involuntary weight loss, organ dysfunction, and frailty 710 31 32 33…”
Section: Discussionmentioning
confidence: 99%
“…29 30 These factors can accelerate the accumulation of unrepaired molecular damage and senescent cells, stimulate the DNA damage response, inhibit stem cell regenerative function, and promote involuntary weight loss, organ dysfunction, and frailty 710 31 32 33…”
Section: Discussionmentioning
confidence: 99%
“…Muscle stem cells (also known as satellite cells) are typically quiescent and start dividing in response to injury or attrition of muscle fibers (myofibers); activated satellite cells then differentiate along the myogenic lineage into fusion-competent proliferating myoblasts (expressing Pax7, MyoD and desmin) and postmitotic multinucleated myotubes (expressing eMyHC), which repair the damaged tissue [19]. Based on our work, type I diabetes has a direct negative effect on the ability of muscle stem cells to activate and regenerate muscle, due to intensified myostatin/ TGF-β receptor/pSmad 3 signaling [3].…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained after heterochronic parabiosis, that is, exposure of an aged organism to a youthful systemic environment, show that failed healing could be attributed not to the stem cells but to the aging process [10]. Identifying systemic differences between old and young may help in achieving molecular control over the niche composition and adequate stem cell activation.…”
Section: Alterations In Paracrine Communication Dynamic Reciprocitymentioning
confidence: 99%
“…Recent research in rejuvenation indicated that the age of the host dictates the success of the approach [10]. The failure of triggering regenerative mechanisms is not attributed to the stem cells but to an old niche, that is, the environment that regulates cell fate.…”
Section: Biological Interventionsmentioning
confidence: 99%
See 1 more Smart Citation